Written Test for Etiqa Takaful - UMP Foundation Excellence Scholarship Offer - Fathiah Izzati, Mohammad Fadzillah (UMPSA, 2021)
15 April 2021 - The Competency Unit of Centre forModern Languages (CML) jointly with the StudentAffairs and Alumni Department (SAffAD)conducted an English Written Test for students whowere shortlisted for Etiqa Takaful - UMP FoundationExcellence Scholarship.